If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3 + -4y) = 0 (3 * 6 + -4y * 6) = 0 (18 + -24y) = 0 Solving 18 + -24y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -24y = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -24y = 0 + -18 -24y = 0 + -18 Combine like terms: 0 + -18 = -18 -24y = -18 Divide each side by '-24'. y = 0.75 Simplifying y = 0.75
| n+29=48 | | -4(-2b-7)=-44 | | 1.84/2.85=5.14/t | | 3i*x=y | | 2(5t-4)+6=40-t | | 49.2=1.5h | | 2(4m+1)=3 | | 114/95=95/x | | 6.4=16y | | xx/7-3=4 | | (2x-7)3=10x-9 | | -43=x/16 | | x-1=6/x | | 6x^3+56=53x-x^2 | | 7=5/6b-8 | | Y^2+3y=x | | (6+4x)*(15x+25)=0 | | F(x)=4*logx | | 3485x^2-311107.5x-18855000=0 | | n/36=17/72 | | 7w+6-3w=6 | | 4(2b-5)=2b+10 | | X/5-7=2 | | 2.3=y+.9 | | 12c-48=84 | | 9x-5=3x+47 | | x(x+13)=40 | | (1+2i)*x+(3-5i)*y=1-3i | | -3=2-(-x/5) | | 14x^2-5x+1=0 | | -12+x=60 | | 7x^2-14x-5=0 |